Relevansi Bahasa Daerah Tontembon dalam Liturgi Kreatif Minggu Ke-5 di Jemaat Gmim Bukit Zaitun Tewasen Wilayah Amurang IV - Lintang, Wulan Teresa; Sarimbangun, Ramli (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
This thesis is to highlight, describe, and analyze the relevance of Tontemboan local language in the creative liturgy of the 5th week in the congregation of GMIM Bukit Zaitun Tewasen Amurang IV Region. The problem that arises is that the congregation has begun to forget the Tontemboan language, which is the mother tongue and the identity of the Bukit Zaitun Tewasen congregation, so the author wants to see the relevance of the Tontemboan regional language. Tontemboan language, as an important element of culture, must be passed down from generation to generation so that the congregation will still recognize it. The advancement of globalization and technological advances is now one of the factors that influence the language culture to begin to erode. Through creative liturgy using the Tontemboan local language, it will provide a new atmosphere for the congregation in worship. The research method used to solve the problem is qualitative research, with stages of collecting scientifically tested literature, such as books and journals, without ignoring field data. The author's view is that the Tontemboan language culture is a wealth that only belongs to the Tontemboan tribe and that we must continue for generations. Being inculturated, Tontemboan language culture is integrated with worship but still runs according to the teachings of the Word of God.